(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The article aims to highlight the contributions of an important illustrator to the scenario of the history of design and illustration in Brazil: Cândido Aragonez de Faria of Sergipe (Brazil). These contributions are presented by means of a rescue of his biography and performance trajectory in the composition of posters for French cinema. It makes use of a documentary and hermeneutic analysis of the historical trajectory of Sergipe’s posterist and questions his trajectory between academic drawing and commercial art and the peripheral situation of Faria as a Northeastern, Brazilian and posterist in a Parisian market to explain his absence in the historiography of design Brazilian. He concludes by emphasizing the innovative role of his techniques in the production of posters.